Selective binding to mRNA duplex regions by chemically modified PNAs stimulates ribosomal frameshifting - Puah, Ru Ying (2018)
Minus-one programmed ribosomal frameshifting (-1 PRF) is a prominent mechanism that exists in ribonucleic acid (RNA) viruses. It allows precise maintenance of ratio between viral structural and enzymatic proteins, and is involved in the regulation of the half-life of cellular messenger ribonucleic acid (mRNAs). Variations made to the narrow window of protein ratio would disrupt the propagation of viral replication. The efficiency of -1 PRF is affected by the stability of the mRNA secondary structure, together with the presence of a slippery site which is located upstream of the secondary element embedded in the mRNA sequence. Peptide nucleic acids (PNAs) were thus, utilized as a ligand to regulate the stability of model mRNA secondary structures, altering the ratio of protein production. PNA strands containing modified nucleobases were designed to target the stem-loop region, forming major-groove parallel PNA·RNA-RNA triplex. They show selective binding to double-stranded RNAs (dsRNAs) over single-stranded RNAs (ssRNAs). In summary, this study suggests that the dsRNA-specific chemically modified PNA stimulate -1 RF in a model mRNA hairpin (from 2% to 32%), demonstrated by using cell-free in vitro translation assays. An unmodified control PNA, however, shows nonspecific inhibition of translation.